Flavonoid induction of cytochrome P450 (CYP) in human esophageal carcinoma cells: implications for chemotherapy - Molepo, Ramaesela Sharon (My University, 2011)
Esophageal cancer ranks as the second most common cancer among black males in South Africa and patients often seek medical attention when the cancer has already reached advanced stages. Thus, there is a lot of work investigating factors associated with increased risk, biomarkers for early diagnosis as well as a search for suitable drugs to treat esophageal cancer. In this project, flavonoids were used on esophageal cancer cell lines to identify enzymes that are differentially expressed as well as to evaluate the flavonoids’ direct toxic effects on the cancer cells using ß-Naphthoflavone (BNF) on human esophageal cancer cell lines, WHCO1 and WHCO6. Differential expression of drug metabolising enzymes, CYP1A1, CYP1A2 and CYP1B1 was also investigated. BNF showed a moderate antiproliferative activity in WHCO6 cells (IC50~ 10μM) and a weak activity in WHCO1 cells (IC50~25 μM). Thus, suggesting that esophageal cancer cells may be responsive to the treatment with BNF. BNF resulted in the differential expression of CYP1A1, CYP1A2, and CYP1B1. These results, implicate CYP1 enzymes as potential therapeutic targets for esophageal cancer prevention.